METHODOLOGICAL DESCRIPTION OF TOOLS FOR DEVELOPING STUDENTS’ WRITING SKILLS IN THE CONTEXT OF DIGITALIZATION - Muydinov Mansurjon Ilhomhon o‘g‘li (TADQIQOTLAR, 2025)
ABSTRACT: This article investigates the methodological principles and tools that support the development of students’ writing skills in the digital era. It focuses on the  pedagogical  potential  of  artificial  intelligence,  digital  learning  platforms,  and multimodal  environments  in  enhancing  linguistic,  communicative,  and  creative competencies. The study emphasizes that integrating technological innovations into writing  instruction  not  only  enriches  language  learning  but  also  fosters  autonomy, collaboration, and critical thinking.